Quand la foule devient peuple … avec Léon Gambetta - Aude Dontenwille-Gerbaud (Conserveries Mémorielles)
From 1870 to 1882 in France, the crowd becomes a central actor in the construction of the Third Republic. The image of the crowd assaulting the Bastille or controlling the barricades is replaced by a crowd cheering the great republican leaders who rely on its support. A sound assessment of Léon Gambetta’s “founding” speeches needs to consider not only their textual content but also their theatrical dimension in order to analyse these events as forerunners of modern politics. As the memory of the revolutionary crowds is persisting in the first years of the Third Republic, the republican crowds catch the attention of actors from all sides of the political spectrum. In this key moment of French history, the republican project is aimed at canalizing the energy of the crowd into the construction of an enlightened people. The contributions of Jürgen Habermas, Claude Lefort and Paul Ricoeur invite us to move over the analysis of a republican idea in order to insist on the actual making of a democratic society.